Methodology of design and hydrodynamic simulation of a Kaplan microturbine using computer tools (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2016)
This paper evaluates a simulation model of a six blades Kaplan microturbine; with this, the effect caused by the pitch variation of the turbine when obtaining power at the output shaft is parametrically analyzed implementing different rotation speeds of the latter, related to the surrounding water flow. The geometry is simplified to reduce the processing time, discretization and the model analysis; the simulation was performed under defined boundary conditions and using computational fluid dynamics. With the data obtained, it was generated a series of 2D and 3D performance curves, that allows to characterize the behavior of the Ka plan microturbine, taking into account the inclination of the blades and the impeller rotation speed, in order to determine the operation ranges in which the highest power output is obtained.
Keywords: Micro generators; hydrodynamic simulation; blades position; Kaplan turbine